Knowledge & Attitudes towards Family Use of Maternal Child Health Handbook - Dharmawan, Yudhy; Mawarni, Atik; Handayani, Novia; Pradana, Atha Rifqia (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
The use of the Maternal and Child Health (MCH) handbook requires family support, but the utilization of the MCH Handbook by the family is still low. The objectives of this research are to know the extent MCH Handbook used by the family and the factors related to it. This is an explanatory research with a cross-sectional design. The study sample is the total population in Kemawi Village, which is 60 families who have pregnant woman or baby or toddler. The results of rank-spearman correlation showed that there is a strong and positive relation between knowledge with the use of MCH Handbook (rs = 0.571, p = 0.0001) and between attitude and the use of MCH Handbook (rs = 0.468, p = 0.0001). Multivariate analysis with binary logistic regression showed that the knowledge (OR =4.9) and attitude (OR=11.9) variables had a significant influenceÃ‚Â together on the use of the MCH handbook with probability is 74.3% . It is suggested to village midwives to increase counseling to the community about MCH Handbook related to motherÃ¢â‚¬â„¢s health in the postpartum period, especially regarding family attitudes towards the MCH Handbook.